EFFICACY AND SAFETY OF AMLODIPINE MALEATE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND BRONCHIAL ASTHMA WITH CONCOMITANT ARTERIAL HYPERTENSION - N. A. Karoli; A. P. Rebrov; A. A. Roshchina; V. A. Sergeeva; E. E. Arkhangelskaya (Столичная издательская компания, 2016)
Aim. To evaluate efficacy and safety of amlodipine maleate in patients with chronic obstructive pulmonary disease (COPD), bronchial asthma (BA) and concomitant arterial hypertension.Methods. Patients (n=40) with COPD (n=20) or BA (n=20) and hypertension of 1-2 degree were examined. Amlodipine maleate was used as antihypertensive drug. The spirometry, ambulatory blood pressure monitoring, vascular oscillometry (evaluation of arterial stiffness), vascular Doppler imaging (evaluation of endothelial function) was performed initially and in 6 months of treatment.Results. The high efficacy of amlodipine maleate as antihypertensive drug was found in patients with COPD or BA and hypertension without dependence on bronchial obstruction severity. The positive influence of amlodipine on endothelial function and vascular rigidity was also observed.Conclusion: study results confirm the rationales of amlodipine use in patients with COPD or BA and hypertension.